ABC Learning: accounting lessons never learned?. (1st January 2012) - Ross, Phil; Sy, Aida; Tinker, Tony
The collapse of ABC Learning (ABC) is replete with lessons for accountants, auditors, executives and regulators. From its early beginnings, ABC's intervention into child care provision, gave plenty of red flags for anyone paying attention. Unfortunately, the euphoria, championed by Australian's new charismatic boy wonder (ABC's Eddie Groves) led a 'free market' mergers-and-acquisition incursion into child care. The chorus of cheer-leaders drowned-out the naysayers. No-one wanted to be branded as a non-believer. As with many high-growth entities that expand by merger and acquisition; they are heavily leveraged bubbles. Eventually, bubbles burst on margin calls. ABC Learning that stretched over several continents, collapsed and the Australian state, who was a founder member of the origin joined the free-market celebrations (giving generous state subsidies to fund their poster boy, Eddie Groves, was left to pick up the pieces by underwriting the rescue package.